Advances and Accuracy Assessment of Ocean Tide Models in the Antarctic Ocean - Weikang Sun; Weikang Sun; Xinghua Zhou; Xinghua Zhou; Dongxu Zhou; Yanfei Sun (Frontiers in Earth Science, 2022)
Ocean tides in polar regions play an important role in the study of sea ice dynamics and floating ice shelves. The accuracy of existing ocean tide models in shallow waters and polar seas is much lower than that in open deep oceans. This study summarized the advances of state-of-the-art global tide models in the Antarctic Ocean, the construction of tide models around Circum-Antarctica, and five typical regions: Antarctic Peninsula, Ross Sea, Filchner–Ronne Ice Shelf (FRIS), Weddell Sea, and Amery Ice Shelf (AIS). The accuracy of FES 2014, TPXO9, EOT20, CATS 2008, and regional tide models in the Antarctic Ocean and typical areas was evaluated using tidal records and satellite altimetry data. EOT20 and ANTPEN04.01 models have higher accuracy in the Antarctic Peninsula, and the root sum square (RSS) values are 8.29 and 7.46 cm, respectively. TPXO9 has the highest accuracy in the Weddell Sea and FRIS and AIS and RSS values are 18.33 and 12.77 cm, respectively. TPXO9 and RIS_Optimal models have higher accuracy in the Ross Sea and Ross Ice Shelf (RIS), RSS values are 5.62 and 6.21 cm, respectively. The accuracy of FES 2014, TPXO9, CATS 2008, and the regional tide model in the Drake Passage, Kerguelen Islands, and Adelie–Mertz was evaluated using satellite altimetry data. The RSS values are less than 4 cm. By using the altimetry data at Sentinel-3A single-satellite crossovers in terms of the STD of the SLA, the comparison of the STDs show that FES2014 is the best.